Respuesta :

Answer:j=7

Step-by-step explanation:

9 times 7 equals 63

Answer:

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    63-(9*j)=0

Step by step solution :

STEP

1

:

Pulling out like terms

1.1     Pull out like factors :

  63 - 9j  =   -9 • (j - 7)

Equation at the end of step

1

:

STEP

2

:

Equations which are never true:

2.1      Solve :    -9   =  0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation:

2.2      Solve  :    j-7 = 0

Add  7  to both sides of the equation :

                     j = 7

solved

j = 7

ACCESS MORE